Mutually Exclusive p‐Type and n‐Type Hybrid Electrode of MoS2 and Graphene for Artificial Soft Touch Fingers. (19th September 2019) - Manzoor, Muhammad Taha; Nguyen, Van Hiep; Umrao, Sima; Kim, Jae‐Hwan; Tabassian, Rassoul; Kim, Ji‐Eun; Oh, Il‐Kwon
Abstract: Future smart mobile electronics and wearable robotics that can perform delicate activities controlled by artificial intelligence can require rapid motion actuators working at low voltages with acceptable safety and improved energy efficiency. Accordingly, ionic soft actuators can have great potential over other counterparts because they exhibit gentle movements at low voltages, less than 2 V. However, these actuators currently show deficient performances at sub‐1 V voltages in the high‐frequency range because of the lack of electrode materials with the vital antagonistic properties of high capacitance and good conductivity. Herein, a mutually exclusive nanohybrid electrode (pMoS2 ‐nSNrGO) is reported consisting of oxide‐doped p‐type molybdenum‐disulfide and sulfur‐nitrogen‐codoped n‐type reduced‐graphene‐oxide. The pMoS2 ‐nSNrGO electrode derives high capacitance from MoS2 and good charge transfer between the two components from p‐n nano‐junctions, resulting in excellent actuation performances (670% improvement compared with rGO electrode at 0.5 V and 1 Hz, together with fast responses up to 15 Hz). With such excellent performances, these actuators can be successfully applied to realize an artificial soft robotic finger system for delicately touching the fragile surfaces of smartphones and tablets. The mutually exclusive pMoS2 ‐nSNrGO electrode can open a new way to develop high‐performance soft actuators for soft robotic applications in the future. Abstract : Nanohybrids with antagonistic properties (high capacitance and good conductivity) like pMoS2 ‐nSNrGO are demonstrated among excellent electrode materials for ionic actuators. With a 670% bending improvement at a low voltage of 0.5 V and the ability to perform fast bending up to 15 Hz, the pMoS2 ‐nSNrGO‐based actuators successfully act as soft fingers to touch fragile surfaces of smartphones to switch the flashlight.